Kendala Implementasi Peraturan Pemerintah No 37 Tahun 2023 Dalam Membangun Desa di Desa Kabupaten Muaro Jambi - Rohana; Martaliaah, Nurfitri; erliyana, Nova (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
This research focuses on villages in Muaro Jambi. This research uses descriptive qualitative research techniques which describe the obstacles faced by each village in implementing Government Regulation No. 37 of 2023. The villages used as research sites are six villages. The data collection technique is by conducting direct interviews with the Village Head. Where the following conclusions were obtained: Obstacles faced by the village government in implementing Government Regulation No. 37 of 2023 in planning village development include 1) lack of land for strengthening food so replacing it with various other alternatives such as raising cattle. Cattle rearing is also not very effective because the community lacks expertise in raising cows, which results in cows dying due to disease. The next obstacle is 2) lack of community participation in taking part in programs carried out by village officials, such as few people present during health education, lack of interest in posyandu and difficulty in getting the community to work together in building village roads. 3) there is still a lack of village funds so that village development is not evenly distributed which causes jealousy. social relations between residents 4) lack of village experts in compiling detailed village financial reports resulting in a long time in compiling village financial reports 5) Lack of skills among residents in carrying out food security innovations and expertise in using land and local wisdom.